Conhecimento de mulheres com deficiência visual sobre o papilomavírus humano e fatores de risco - Inacia Sátiro Xavier de França; Caroline Gomes Maciel; Jamilly da Silva Aragão; Alexsandro Silva Coura; Aldenice Oliveira dos Santos; Arthur Felipe Rodrigues Silva (Universidade Federal do Ceará, 2017)
Objective: to identify the knowledge of women visual impairment about the human papillomavirus and its association with risk factors. Methods: cross-sectional study with 29 women with visual impairment using a questionnaire containing demographic variables, risk factors and knowledge about the human papillomavirus. The analysis was performed using analytical and descriptive statistics, Fisher's test, considering the significance level of 5%. Results: most participants said that they had already heard about the human papillomavirus (86.2%). One verified an association between the knowledge about the virus and the age of first sexual intercourse, the preventive Papanicolaou test and the frequency and use of condom. Conclusion: women with visual impairment, although with limitations, show knowledge about the human papillomavirus. This knowledge was associated with risk factors.